Developing an Effective Preparation Strategy Model for Competency Tests in Heavy Equipment Engineering at Vocational High Schools - Albar Riadi; C. Rudy Prihantono; Imam Basori (Journal of Pedagogi, 2024)
This study aims to develop an effective preparation strategy model for competency tests in Heavy Equipment Engineering at vocational high schools. Recognizing the pivotal role of vocational education in equipping students with industry-relevant skills, the research addresses the challenges students face in preparing for competency assessments. Utilizing a mixed-methods approach, the study integrates quantitative data from surveys and pre/post-tests with qualitative insights from interviews and focus groups. The proposed model encompasses curriculum alignment, innovative teaching methodologies, and effective study techniques, incorporating best practices identified through an extensive literature review. Pilot testing in selected schools provided critical feedback, allowing for refinements to ensure the model's applicability and effectiveness. The evaluation of the model's impact revealed significant improvements in students' test scores and self-reported preparedness, demonstrating the model's potential to enhance competency levels. Comparative analysis highlighted the model's superiority over traditional preparation methods, while qualitative feedback underscored its strengths and areas for further enhancement. The findings contribute to the field of vocational education by offering a structured preparation strategy that can be adopted by schools and policymakers to improve student outcomes. The study's implications extend to educational authorities, providing a framework for policy formulation and implementation. Future research directions include refining the model and exploring its applicability across different vocational disciplines.